Raising awareness in the industry on secure code review practices - Iosif, A.-C. (2023)
As products and services become increasingly digital and software increasingly complex, all aspects of an industrial software development lifecycle must contribute to quality. Code review serves as a means to address software quality and fosters knowledge exchange across teams. Nonetheless, code review practices require resources and often require more resources than planned, while the benefit of a code review to code quality is less tangible. In our work, we address the effectiveness and efficiency of code review practices and develop an understanding of what is a good and valuable code review practice as part of a software development lifecycle. Our focus is code reviews meant to identify and address security weaknesses in an industrial context. This work presents a design study on how to design a workshop on code review. We conducted and evaluated three workshops with 37 industrial software developers. The findings of our work reveal that presenting constructive code review practices can contribute to raising awareness of secure coding and software lifecycle practices among software development professionals. This contributes to the quality and, in particular, security of software.